Effects of short video addiction on college students’ physical activity: the chain mediating role of self-efficacy and procrastination - Zhao, Zhe; Kou, Yali (Frontiers in Psychology, 2024)
Excessive use of short video applications can adversely affect the physical and mental health of college students. At present, regarding the effect of short video addiction on physical exercise, few scholars have studied the mechanism of action.This study aims to investigate the mechanism by which short video addiction impacts college students' physical exercise. Therefore, we investigated the correlation between short video addiction and physical activity, and examined the influence of self-efficacy and procrastination on this relationship. In this research, 304 college students were selected as survey subjects. The questionnaires included Short Video Addiction Scale, Physical Activity Rating Scale, General Self-Efficacy Scale, and Short Version General Procrastination Scale. The data underwent correlation analysis using SPSS and mediation effect analysis using the PROCESS macro program.Results: 1) 61.51% (187) of college students' physical activity was low exercise. 2) Physical activity was significantly negatively impacted by short video addiction. 3) Self-efficacy played an independent mediating role in the association between short video addiction and physical activity. 4) The association between short video addiction and physical activity was independently mediated by procrastination. 5) Self-efficacy and procrastination function as chain mediators in the association between short video addiction and physical activity. Our research identifies the role that self-efficacy and procrastination play in the connection between short video addiction and physical activity. Decreasing the utilization of short video applications and enhancing self-efficacy can reduce procrastination and improve physical activity for college student groups.